2011
DOI: 10.3109/19401736.2010.537748
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating DNA barcodes into a multi-year inventory of the fishes of the hyperdiverse Lower Congo River, with a multi-gene performance assessment of the genusLabeoas a case study

Abstract: Background and aims: Here we describe preliminary efforts to integrate DNA barcoding into an ongoing inventory of the Lower Congo River (LCR) ichthyofauna. The 350 km stretch of the LCR from Pool Malebo to Boma includes the world's largest river rapids. The LCR ichthyofauna is hyperdiverse and rich in endemism due to high habitat heterogeneity, numerous dispersal barriers, and its downstream location in the basin. Materials and methods: We have documented 328 species from the LCR, 25% of which are thought to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 42 publications
2
69
1
Order By: Relevance
“…The genetic distances between many of the lineages, even within the 'a priori' species, were substantial. Sometimes they even reached almost 20%, which is considerably larger compared to most other African freshwater fish taxa, that usually have interspecific divergences lower than or around 10% for the COI gene (see, e.g., Lowenstein et al 2011;Decru et al 2016). Only three of the four 'a priori' species agreed with supported clades in our ML tree, i.e., E. cf.…”
Section: Multidisciplinary Approach To Detect Cryptic Speciesmentioning
confidence: 70%
“…The genetic distances between many of the lineages, even within the 'a priori' species, were substantial. Sometimes they even reached almost 20%, which is considerably larger compared to most other African freshwater fish taxa, that usually have interspecific divergences lower than or around 10% for the COI gene (see, e.g., Lowenstein et al 2011;Decru et al 2016). Only three of the four 'a priori' species agreed with supported clades in our ML tree, i.e., E. cf.…”
Section: Multidisciplinary Approach To Detect Cryptic Speciesmentioning
confidence: 70%
“…Yet the broad realization of benefits is predicated on a sustained effort to complete the construction of reference sequence library, which is the major focus of many articles in this special issue. From Africa (Lowenstein et al 2011;Nwani et al 2011) and Europe (Triantafyllidis et al 2011), to Oceania (Smith et al 2011) and South America (Carvalho et al 2011b;Pereira et al 2011a,b), a large number of researchers have contributed to this volume and to the FISH-BOL campaign.…”
mentioning
confidence: 99%
“…billfishes; Hanner et al 2011b) to the challenges of library construction when sampling nominal species far removed from original type localities (e.g. Lowenstein et al 2011). These issues not withstanding, the papers here reinforce the point that the great majority of fish species are easily distinguished using barcodes, and that the maturity of the FISH-BOL campaign is such that it can already support a diversity of applications.…”
mentioning
confidence: 99%
“…In addition to the changes in work flow there have been significant impacts, from finding cryptic species to matching dimorphic males and females, which have substantially improved the quality and depth of the inventory, but also greatly multiplied the number of situations requiring further taxonomic work for resolution. Although the workflow issues differ between different habitats and taxa, other studies have demonstrated the use of barcoding in inventories of diverse taxa, including poorly known freshwater invertebrates (Zhou et al, 2009;Laforest et al, 2013), tropical sand flies (Azpurua et al, 2010;Krüger et al, 2011), bats in Southeast Asia (Francis et al, 2010), difficult to distinguish agricultural pest moths (Roe et al, 2006), pollinating insects in Africa (Nzeduru et al, 2012), diverse radiations of tropical weevils (Pinzón-Navarro et al, 2010a, 2010bTänzler et al, 2012), freshwater fishes in Africa (Swartz et al, 2008;Lowenstein et al, 2011), butterflies at country scales (Dinca et al, 2011;Hausmann et al, 2011), amphibians in Panama (Crawford et al, 2010) and trees in forest plots (Kress et al, 2009(Kress et al, , 2010Costion et al, 2011). Perhaps even greater opportunities for improving the speed and quality of inventories exist in the marine realm, where poorly known larval stages exist in vast quantities, and species concepts must be compared across vast oceanic distances (Goetze, 2010;Heimeier et al, 2010;Hubert et al, 2010;Stern et al, 2010;Plaisance et al, 2011;Ranasinghe et al, 2012).…”
Section: How Does Barcoding Change the Approach To An Inventory?mentioning
confidence: 99%